Sustainable diets and cancer: a systematic review and meta-analysis - Kasper, Marina; al Masri, Mirna; Kühn, Tilman; Rohrmann, Sabine; Wirnitzer, Katharina; Leitzmann, Michael; Jochem, Carmen (EClinicalMedicine, 2025)
Background - Sustainable diets are increasingly recommended as a strategy to reduce non-communicable diseases and promote planetary health. Current unhealthy dietary patterns are thought to contribute to the global cancer burden while food systems continue to exacerbate environmental challenges. Investigating the impact of sustainable diets on cancer is therefore critical. - Methods - This systematic review and meta-analysis included observational studies of healthy adults at baseline, reporting cancer incidence or cancer mortality during follow-up. Eligible studies were identified through a comprehensive search of multiple databases, including PubMed, ISI Web of Science, EMBASE, and the Cochrane Library from inception to February 28, 2025. Sustainable diets were assessed using various metrics, and effect measures were pooled to compare adherence to sustainable dietary patterns. Summary effect estimates for cancer incidence and mortality were calculated using random-effects models. Subgroup analyses were conducted for sex, geographic regions, study design, sustainability metrics, dietary assessment indices on sustainability, cancer types, and dietary energy intake adjustment. E-values were used to assess the robustness of associations against potential unmeasured confounding. The study was pre-registered in PROSPERO (ID CRD42024545102). - Findings - We pooled 19 effect estimates from 17 studies, identified through the literature search. These studies encompassed over 2·2 million participants, with studies spanning from 1983 to 2022. Adherence to sustainable diets revealed a significant reduction in cancer incidence (RE = 0·93 [95% CI 0·88-0·98], I2 = 84·67%) and cancer mortality (HR = 0·88; 95% CI 0·85-0·92, I2 = 21·25%). Subgroup analyses indicated that the overall effect was modified by study region and design, sustainability metrics and dietary assessment indices. High heterogeneity, risk of bias in some studies, and e-values indicating potential residual confounding resulted in an overall low level of evidence as evaluated using GRADE. - Interpretation - These findings provide pooled evidence linking sustainable diets to reduced cancer incidence and mortality, highlighting their potential for cancer prevention and their dual health and environmental benefits. This analysis also revealed notable differences in sustainability metrics, emphasizing the need for standardized approaches. - Funding - This research received no external funding.
Online verfügbar: 29. April 2025, Artikelversion: 21. Mai 2025
Gesehen am 23.09.2025